Penerapan Reliability Centered Maintenance (RCM) Untuk Penentuan Strategi Perawatan Vacuum Pump Autoclave di Industri Farmasi - Daffa Padilah; Yuro Darmawan; Yulin Surbakti; Rajendra Alfarisy; Riki Ridwan Margana (Cakrawala Repositori IMWI)
Autoclaves are critical equipment in the pharmaceutical industry because they play a direct role in ensuring the success of the sterilization process. At PT X, disruptions to the vacuum pump subsystem often cause process delays and potentially interfere with the validity of sterilization. This study aims to analyze the vacuum pump autoclave maintenance system and determine the most appropriate maintenance strategy using the Reliability Centered Maintenance (RCM) method. The study used a case study approach with secondary data in the form of damage history, failure frequency, and duration of downtime. The results of the data processing showed that the shaft seal and control/sensor panel had a relatively high frequency of damage, 2 and 1.25 times per year, respectively, with MTBF values of 182.5 days and 292 days. Meanwhile, the electric motor has a very high MTBF (35,040 hours) and Availability close to 0.999, but it causes a Downtime of up to 36 hours in the event of a failure. Based on the RCM analysis, preventive maintenance strategies are recommended for components with repeated failures, while condition-based maintenance is more appropriately applied to bearings and vanes. The results of the study prove that the application of RCM is able to produce a more targeted, risk-based treatment strategy and support the reliability of the sterilization process according to pharmaceutical industry standards.